Materials Coatings and Enhanced Characterisation for Alkaline Water-Splitting Devices - Bill Gannon (2021)
A number of material coatings were investigated, specifically for 316-grade stainlesssteel electrodes, for use with alkaline water-splitting electrolysis. The aim was to enhancelongevity, particularly with respect to the highly intermittent usage that is typical of renewableenergy generation, and to increase activity. Long-term experiments were conductedover many thousands of cycles of on-off accelerated ageing at constant current density. Theeffects of ageing were analysed using chronopotentiometry, cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), scanning electron microscopy, energy dispersivex-ray spectroscopy, x-ray photoelectron spectroscopy and gas chromatography. It was foundthat titanium nitride did not have high activity for the hydrogen evolution reaction (HER),and underwent rapid oxidation and destruction if used as an anode. A new version ofelectrodeposited Raney nickel was developed that demonstrated improved activity, includingan overpotential for the HER at 10mAcm-2 of just 28 mV. As a bifunctional catalystit demonstrated an overpotential at 10mAcm-2 of just 319 mV, making it the second mostactive catalyst known, and certainly the simplest to deposit. This activity was traced to theincreased electrochemical surface area of the coating, which was higher as deposited, andincreased by up to a factor of three after ageing. During surface-area measurements, anapparent anomaly was discovered between results obtained for the same electrode via EISand CV. New methods of equivalent circuit fitting to transient waveforms were developed,and the anomaly was explained by time-domain simulations of the constant-phase elementrepresentation of the double-layer capacitance. A zero-gap electrolyser was constructed inorder to investigate its performance, and it was found that woven stainless-steel mesh couldoperate as a gas-separation membrane.